Educational Robotics and empowerment of executive cognitive processes: from typical development to special educational needs - Emanuela Castro; Maria Di Lieto; Chiara Pecini; Emanuela Inguaggiato; Francesca Cecchi; Paolo Dario; Giovanni Cioni; Giuseppina Sgandurra (Firenze University Press, 2019)
This paper describes a new Educational Robotic (ER) approach aimed to empower higher cognitive functions in school-setting. As robot programming requires to mentally plan a complex sequence of actions before the motor act, ER may indeed promote several crucial cognitive processes underlying learning. The steps needed and the mental acts for robot programming may involve Executive Functions (EF), that are complex higher cognitive processes, particularly crucial in the early development, because they are the base for abstraction and logical reasoning, decision-making, sequential thinking, maintaining and updating information in memory and problem-solving. Recent studies attempting to attest with a scientific approach the effect of ER on executive functioning are described. They concern both classroom with typical development or special educational needs and rehabilitation environment for children with developmental disorder.   Robotica Educativa e potenziamento dei processi cognitivi esecutivi: dallo sviluppo tipico ai bisogni educativi speciali Il presente lavoro descrive come la Robotica Educativa (RE) possa essere utilizzata per potenziare alcune funzioni cognitive di controllo. Le azioni necessarie e gli atti mentali per la programmazione di un robot implicano le Funzioni Esecutive (FE), processi cognitivi di alto ordine, particolarmente importanti durante lo sviluppo cognitivo perché coinvolti nel ragionamento logico e nell'astrazione, nel decision-making, nel pensiero sequenziale, nel problem-solving e nel mantenimento/ aggiornamento delle informazioni in memoria. Nell'articolo sono sintetizzati e discussi gli studi con cui abbiamo cercato di provare con metodi scientifici l'effetto della RE sulle FE, nel gruppo classe per bambini con sviluppo tipico o con bisogni educativi speciali, e in ambito riabilitativo per bambini con disturbo del neurosviluppo.